Integrating Pantomime Learning in Higher Education: A Case Study of Theater Programs in Indonesia - Hasyim Asyary; Syeilendra Syeilendra; Rini Sefriani (Pedagogy Review, 2026)
It is suspected that pantomime learning in the pantomime theater course is still not running optimally; this was discovered during observations. This study aims to analyze the implementation of pantomime learning applications in the Pantomime Theater course within the Dance and Drama Study Program at Universitas Negeri Padang, Indonesia, and their impact on students' competencies. The study used a qualitative approach with a descriptive case study strategy. Data collection was carried out through observation, in-depth interviews, documentation, and literature review. The informants in this study consisted of lecturers in charge of the course, students, and learning support staff. Based on data analysis and observations, as well as interviews with informants, information was obtained and presented as research results. The results showed that pantomime learning was carried out through an integration of modern methods with the corporeal mime approach developed by figures such as Étienne Decroux and Marcel Marceau. In the learning process, learning tools were designed, including a syllabus and a systematic Semester Learning Plan, and implemented across three main stages: introduction, core, and closing. The learning media used to support learning are video tutorials and direct practice, which can support the improvement of students' understanding visually and kinesthetically. To conduct the assessment, a holistic learning evaluation is carried out by considering various components and specific aspects such as technical aspects, expression, creativity, and understanding of theater concepts. While the main supporting factors include campus facilities and practical activities, research and observations found several obstacles, including low student motivation, limited time available for practice, and a lack of understanding of theory among students. The solution implemented is the integration of theory and practice, and the strengthening of independent learning. Thus, the harmony between theory and practice in pantomime learning can be maximized in the future and become a concern and consideration for the lecturer in charge of the course.Keywords: Pantomime learning, Theater education, Instructional application, Corporeal mime, Performing arts education